2016
DOI: 10.1111/nmo.12846
|View full text |Cite
|
Sign up to set email alerts
|

The role of combined 24‐h multichannel intraluminal impedance‐pH monitoring in the evaluation of children with gastrointestinal symptoms suggesting gastro‐esophageal reflux disease

Abstract: Compared with pH-metry alone, pH-MII performed significantly better in the detection of GERD in all age groups. On the basis of our data, pH-MII had a strong correlation with endoscopically confirmed esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 13 publications
4
37
3
Order By: Relevance
“…Hojsak et al showed that 52.3% children with GI symptoms and pathological pH-MII findings would not be identified by pH metry only, without significant differences between age groups (14). Another study indicated the lowest value of sensitivity in infants (59.4%), and the highest in children over 8 years (76.4%) (25).…”
Section: Combined Ph-mii Monitoring: Advantages and Disadvantagesmentioning
confidence: 98%
See 3 more Smart Citations
“…Hojsak et al showed that 52.3% children with GI symptoms and pathological pH-MII findings would not be identified by pH metry only, without significant differences between age groups (14). Another study indicated the lowest value of sensitivity in infants (59.4%), and the highest in children over 8 years (76.4%) (25).…”
Section: Combined Ph-mii Monitoring: Advantages and Disadvantagesmentioning
confidence: 98%
“…In the recommendations of European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) and North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN), pH-MII monitoring has been recognized as a superior diagnostic method than conventional pH monitoring and it is recommended to be used, instead of pH monitoring in children (1). Afterwards, several studies have shown that combined pH-MII monitoring is a more sensitive method for detecting RE than pH monitoring alone (5,14). It is now clear that a significant percentage of RE in infants and children is weakly acidic, and that weakly-acid reflux causes symptoms (5,14,15).…”
Section: Combined Ph-mii Monitoring: Advantages and Disadvantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…This method detects reflux in the pH below 4, but GER episodes of weak acidity are not detected with this method. Neonates, infants and neurologically impaired children tend to have weak acid reflux because of the frequent feeding and neutralization of the gastric content following milk or formula [6][7][8] . Therefore, it is not possible to detect all reflux episodes with pH monitoring.…”
mentioning
confidence: 99%